Loan Restructuring, Human Capital and Digital towards MSME Performance in the COVID-19 Pandemic - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi (APMBA (Asia Pacific Management and Business Application), 2021)
The contribution of MSMEs in the Indonesian economic during the Covid-19 pandemic contribute to the stability of the economic. The purpose of this study was to determine the effect of restructuring people’s business loans (KUR/Kredit Usaha Rakyat), human capital and the digital ecosystem on the performance of MSMEs during the COVID-19 pandemic. This quantitative research method uses primary data obtained from questionnaire data and measured by a Likert scale. The population of this research is SMEs using KUR in Bali Province as many as 21,570, and the research sample obtained as many as 350 MSMEs samples. Questionnaires as research data were collected and distributed online in the google form and processed by multiple linear regression analysis using SPSS version 23. This study shows that the restructuring of KUR, human capital and digital ecosystems has a positive and significant impact on the performance of MSMEs during the pandemic COVID-19. They support its performance, including MSMEs, which can have superior human resources or human capital, to have a competitive advantage. Indicators of human capital that can improve MSME performance, especially financial performance, are knowledge, abilities and skills. Government regulations through the Financial Services Authority (OJK) have shown positive results. The government is trying to ease the burden on MSMEs by providing credit restructuring, interest subsidies, and loans through banks. Some MSMEs began to show improvement in their performance, one of which was financial performance.